2012
DOI: 10.1128/aem.00477-12
|View full text |Cite
|
Sign up to set email alerts
|

Human Milk Oligosaccharides Promote the Growth of Staphylococci

Abstract: f Human milk oligosaccharides (HMO), which constitute a major component of human milk, promote the growth of particular bacterial species in the infant's gastrointestinal tract. We hypothesized that HMO also interact with the bacterial communities present in human milk. To test this hypothesis, two experiments were conducted. First, milk samples were collected from healthy women (n ‫؍‬ 16); culture-independent analysis of the bacterial communities was performed, HMO content was analyzed, and the relation betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
69
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(82 citation statements)
references
References 40 publications
7
69
0
5
Order By: Relevance
“…on HMOs. Hunt et al (2012) reported that HMOs have growth-stimulating properties on Staphylococcus aureus and Staphylococcus epidermidis ; however, analysis showed no HMO consumption from the spent media, suggesting factors other than HMOs caused the growth stimulation. Bacteroides thetaiotaomicron and Bacteroides fragilis utilize HMOs by inducing the same genes that are involved in mucin utilization (Marcobal et al 2011).…”
Section: Structure-function Associations Of Milk Glycansmentioning
confidence: 98%
“…on HMOs. Hunt et al (2012) reported that HMOs have growth-stimulating properties on Staphylococcus aureus and Staphylococcus epidermidis ; however, analysis showed no HMO consumption from the spent media, suggesting factors other than HMOs caused the growth stimulation. Bacteroides thetaiotaomicron and Bacteroides fragilis utilize HMOs by inducing the same genes that are involved in mucin utilization (Marcobal et al 2011).…”
Section: Structure-function Associations Of Milk Glycansmentioning
confidence: 98%
“…A number of basic cosmetics contain oligosaccharides to facilitate the colonization of S. epidermidis; however, they also have the undesirable property of promoting the growth of S. aureus [12]. In contrast, the continuous application of individualized S. epidermidis samples has the advantage of leading to only a specific increase in S. epidermidis.…”
Section: Application Of S Epidermidis Samples To Skinmentioning
confidence: 98%
“…Thus, numerous basic cosmetics that facilitate the growth of S. epidermidis on the skin surface have been developed to exploit the skin care benefits induced by S. epidermidis. However, the stimulating effects of these basic cosmetics on the colonization of S. epidermidis are often insufficient because of the differences in the skin characteristics of individuals and the gradual depletion of active substances in basic cosmetics induced by the metabolism of the skin microbiota itself [12].…”
Section: Introductionmentioning
confidence: 99%
“…75 Additional in vitro data suggests that the supplementation of infant formula with human milk oligosaccharides enhanced growth of opportunistic pathogens S. aureus and Staphylococcus epidermidis, and culture-independent data correlates concentrations of human milk oligosaccharides with the presence of Staphylococcus species in human milk samples. 76 A small clinical trial of formula enriched with galacto-oligosaccharide or human milk oligosaccharide from donor milk administered to premature infants reported no appreciable difference in stool bacterial composition, noting that antibiotic use was widespread among the research subjects. 77 Limited supply currently precludes extensive trials of human milk oligosaccharides as prebiotic agents in humans and animals.…”
Section: Prebiotic Oligosaccharidesmentioning
confidence: 99%